The age of absurdity : why modern life makes it hard to be happy - Foley, Michael, ....- (London : Simon & Schuster, 2011)
In a world that demands conspicuous consumption, high-octane relationships and perpetual youth, we can find ourselves tormented by dissatisfaction and anxiety, fearful that everyone is having a better time than we are. This thorny problem of happiness is the subject of Michael Foley's entertaining and witty investigation into how fulfillment eludes us as we work, love and grow old in the twenty-first century. Drawing on a wide range of sources, from the earliest writings to the latest research in psychology, Foley sheds ironic light on the absurd nature of contemporary cultural conditioning. In conclusion, rather than denouncing and rejecting our age, he proposes a strategy of not just accepting but embracing modern life - by learning that absurdity is the new sublime.
Keywords: Geluk; Welvaarstheorie; Welvaartskritiek